login
Constant term of the reduction (by x^2->x+1) of polynomial p(n,x) identified in Comments.
2

%I #9 Jan 17 2013 09:05:23

%S 1,0,3,4,25,68,275,904,3297,11400,40499,141900,500697,1760396,6200675,

%T 21820432,76823425,270407696,951914403,3350807700,11795463001,

%U 41521535700,146162319603,514512119704,1811159622625,6375545788568,22442862753875

%N Constant term of the reduction (by x^2->x+1) of polynomial p(n,x) identified in Comments.

%C To define the polynomials p(n,x), let d=sqrt(x+2); then p(n,x)=(1/2)((x+d)^n+(x-d)^n). These are similar to polynomials at A161516.

%C For an introduction to reductions of polynomials by substitutions such as x^2->x+1, see A192232.

%F Conjecture: a(n) = 2*a(n-1)+6*a(n-2)-2*a(n-3)-a(n-4). G.f.: -x*(x+1)*(3*x-1) / (x^4+2*x^3-6*x^2-2*x+1). [_Colin Barker_, Jan 17 2013]

%e The first four polynomials p(n,x) and their reductions are as follows:

%e p(0,x)=1 -> 1

%e p(1,x)=x -> x

%e p(2,x)=2+x+x^2 -> 3+2x

%e p(3,x)=6x+3x^2+x^3 -> 4+11x.

%e From these, we read

%e A192346=(1,0,3,4,...) and A192347=(1,1,2,11...)

%t q[x_] := x + 1; d = Sqrt[x + 2];

%t p[n_, x_] := ((x + d)^n + (x - d)^n )/ 2

%t (* similar to polynomials defined at A161516 *)

%t Table[Expand[p[n, x]], {n, 0, 4}]

%t reductionRules = {x^y_?EvenQ -> q[x]^(y/2),

%t x^y_?OddQ -> x q[x]^((y - 1)/2)};

%t t = Table[Last[Most[FixedPointList[Expand[#1 /. reductionRules] &, p[n, x]]]], {n, 0, 30}]

%t Table[Coefficient[Part[t, n], x, 0], {n, 1, 30}]

%t (* A192346 *)

%t Table[Coefficient[Part[t, n], x, 1], {n, 1, 30}]

%t (* A192347 *)

%Y Cf. A192232, A192347.

%K nonn

%O 1,3

%A _Clark Kimberling_, Jun 28 2011